A contribution to the biology of Tilapia mossambica Peters in Lake Sibaya, South Africa - Bruton, Michael N (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1973)
An account is given of some aspects of the biology of Tilapia mossambica Peters in Lake Sibaya, South Africa. Previous work on Tilapia in Lake Sibaya is reviewed. Apart from brief gillnet surveys, which recorded the species' presence, no research on T. mossambica had been performed at Lake Sibaya before the two-year study of Minshull who collected data on food preferences, depth distribution of juveniles and breeding biology of adults. The main physiographical features of the lake are outlined. Lake Sibaya is a warm shallow coastal lake with extensive shallow terraces in the littoral which shelve abruptly into underwater valleys. The substrate is predominantly sandy. Aquatic macrophytes are generally restricted to water 1-7 m deep. Adult fishes (over 8 cm SL) are usually absent from water deeper than 12 m and shallower than 0.5 m, whereas juveniles may occur at all depths, and fry only in very shallow water. T. mossambica inhabits the littoral in the warm and transition periods (August to April) but moves into deep water in the cool season (May to July). Exposed and sheltered shallow areas are utilised for different purposes by adult fishes, the former for nesting, and the latter for feeding and mouth-brooding. Habitat selection by males was governed by nest site selection. Habitat Nests were most common in sheltered, sparsely vegetated littoral and sublittoral areas, but also present in well-vegetated sheltered areas. Breeding females preferred sheltered littoral areas but ventured onto the terrace to release the young. Juvenile and fry T. mossambica inhabited shallow exposed shores with a temperature gradient which reversed diurnally. The breeding, shoaling and feeding behaviour of T. mossambica is described, and integrated with data on T. mossambica from other systems. The breeding season spans seven months. Shoaling takes place in shallow water probably as a means of protection. T. mossambica is an omnivorous feeder relying largely on diatoms. The main predator is probably the barbel Clarias gariepinus, but avian predators may be more important. A method whereby the time of formation of rings on the scales of T. mossambica is described. The fishes were found to reach maturity after one year at a length of about 8 cm in females, and after two years at 10 cm in males. The breeding population had a standard length mode of 14 cm (females) and 17 cm (males). The maximum final size was about 24 cm SL. An estimate of the standing crop for fishes in the littoral and subiittoral areas of the eastern and southern shores of the south basin is given. The data were derived from a mark and recapture The biology of T. mossambica in Lake Sibaya as revealed by the present study is discussed with reference to data on the same and similar species in other systems. The utilis ation of the available resources in the lake by T. mossambica is commented upon, and reference is made to the significance of stunting, and the import ance of the retention of generalised characters for the successful habitation of the cyclically-renewed habitat of the littoral. Precocious breeding in T. mossambica is regarded as a functional adaptation which increases the proportion of fishes small enough to utilise the rich food resources in shallow water.
Keywords: Cichlids; Tilapia; Mozambique tilapia